Derivatives of 16alpha-hydroxy-dehydroepiandrosterone with an additional 7-oxo or 7-hydroxy substituent: synthesis and gas chromatography/mass spectrometry analysis - Pouzar, Vladimír; Černý, Ivan; Hill, Martin; Bičíková, Marie; Hampl, Richard (Steroids, 2005)
Derivatives of 16alpha-hydroxy-dehydroepiandrosterone, which have an additional oxygen substituent at position 7 (oxo or hydroxy group), were synthesized. Firstly, 17,17-dimethoxyandrost-5-ene-3beta,16alpha-diyl diacetate was prepared and then oxidized with a complex of chromium(VI) oxide and 2,5-dimethylpyrazole to the respective 7-oxo derivative. This key intermediate was both deprotected or reduced by l-Selectride or sodium borohydride in the presence of cerium(III) chloride and then deprotected to give 7-oxo, 7alpha-hydroxy and 7beta-hydroxy derivatives of 16alpha-hydroxy-dehydroepiandrosterone. The target compounds were characterized by (1)H and (13)C NMR spectra and in the form of O-methyloxime-trimethylsilyl derivatives, by gas chromatography/mass spectrometry methods.
Keywords: financování organizované; Hydroxylation; chloridy; indikátory a reagencie; Molecular Structure; Indicators and Reagents; dehydroepiandrosteron; Financing, Organized; magnetická rezonanční spektroskopie; molekulární struktura; oxidace-redukce; Dehydroepiandrosterone; Oxidation-Reduction; plynová chromatografie s hmotnostně spektrometrickou detekcí; Gas Chromatography-Mass Spectrometry; Borohydrides; Cerium; borohydridy; Magnetic Resonance Spectroscopy; hydroxylace; Chlorides; cer